From Geophysics to Microgeophysics for Engineering and Cultural Heritage. (30th May 2011) - Cosentino, P. L.; Capizzi, P.; Martorana, R.; Messina, P.; Schiavone, S.
Abstract : The methodologies of microgeophysics have been derived from the geophysical ones, for the sake of solving specific diagnostic and/or monitoring problems regarding civil engineering and cultural heritage studies. Generally, the investigations are carried out using different 2D and 3D tomographic approaches as well as different energy sources: sonic and ultrasonic waves, electromagnetic (inductive and impulsive) sources, electric potential fields, and infrared emission. Many efforts have been made to modify instruments and procedures in order to improve the resolution of the surveys as well as to significantly reduce the time of the measurements without any loss of information. This last point has been achieved by using multichannel systems. Finally, some applications are presented, and the results seem to be very promising and promote this new branch of geophysics. Therefore, these methodologies can be used even more to diagnose, monitor, and safeguard not only engineering buildings and/or large structures, but also ancient monuments and cultural artifacts, such as pottery, statues, and so forth.